MODALITY IN LINGUISTIC BEHAVIOR IN TRANSLATION OF AL-MULK: PRAGMATIC ANALYSIS - Riza Lupi Ardiati, Pika Yestia Ginanjar, Kasno Pamungkas, Titin Nurhayati Ma’mun (Hamdard Islamicus, 2020)
This research aims to analyze the modalities contained in the Al-Mulk, using the Pragmatics Leech and Searle in Rahardi (2003) and Alwi (1992) approaches, as well as descriptive analytical methods. Leech proposed four types of illocutionary related to social goals and maintenance of linguistic behavior, while Searle revealed five illocutionaries based on the criteria. The results of the study found that in Al Mulk's there is a modalitay that refers to what was stated by Leech and Searle, that is convivial behavior in expressive illocutionary of praising propositions, and commissive illocutionary in the offers proposition. Furthermore, conflictive behavior on expressive illocutionary is found in the form of threatening propositions. Next, competitive behavior in expressive illocution is found in the form of warning propositions. On the other hand, competitive behavior also exists in the directive illocutionary in the form of an ordered proposition, then the begging proposition. Collaborative behavior in directive teaching illocutionary is also found.